Application of SAVI’s Model To Improve The Quality of Process And Student Learning Achievement of Vocational High School - Dining Tyas Ariana; Abdul Haris Setiawan; Anis Rahmawati (Indonesian Journal Of Civil Engineering Education, 2016)
h: 0px; "> This research aims to: (1) determine the application of SAVI’s modelto improve the quality of process and student learning achievement (2) determine the improvement of quality learning process (3) determine the improvement of student learning achievement in building construction subject in tenth grade Civil Engineering at SMKN 2 Surakarta. This research used Classroom Action Research (CAR). The research were conducted in two cycles, with each cycle consisting of planning, implementation, observation and reflection. Data collection techniques using observation, interviews, documentation, and tests.The validity test of the data using data triangulation and data analysis using descriptive analysis. The result showed that (1) application of SAVI’s model in classroom has been done well (2) SAVI’s model can improve the quality of learning process in classroom (3) SAVI’s model can improve the student learning achievement in classroom. This means, after the application of SAVI’s model in classroom of X TGBA quality process and student learning achievement were increased. Students became more independent at learning.Keywords: SAVI